(3GdeQTO GdeYjf Ydi GdVQhQi ef Ydhe GdOjfs - (3YHO GdhGMO Hf CMeO Hf Ydj Hf YGTQ GdCfUGQj,J (B1040 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jbhd YHO GdhGMO GHf YGTQ eHJOFkG HGSe GdEdg GdbGOQ GdMeO ddg GdPi YdefG ef GdYdhe eG Hg cadfG s
(3BNQgG (B:s
(3hYSd aGcgI eY GdNVQ EPgHi ai GdebJGJ eeG jONQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B467s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs